2016
DOI: 10.1016/j.nicl.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of MR markers for differentiating Progressive Supranuclear Palsy from Parkinson's disease

Abstract: BackgroundAdvanced brain MR techniques are useful tools for differentiating Progressive Supranuclear Palsy from Parkinson's disease, although time-consuming and unlikely to be used all together in routine clinical work. We aimed to compare the diagnostic accuracy of quantitative morphometric, volumetric and DTI metrics for differentiating Progressive Supranuclear Palsy-Richardson's Syndrome from Parkinson's disease.Methods23 Progressive Supranuclear Palsy-Richardson's Syndrome and 42 Parkinson's disease patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 31 publications
6
65
1
1
Order By: Relevance
“…7, 8, 35, 39 Whereas most studies report increased MD values in the PUT of PSP patients. 35, 39, 40 we did not detect MD changes in the PUT or other basal ganglia structures (CN and GP) in the current study. Consistent with our findings, Tsukamoto et al reported no MD changes in the PUT of PSP patients.…”
Section: Discussioncontrasting
confidence: 79%
“…7, 8, 35, 39 Whereas most studies report increased MD values in the PUT of PSP patients. 35, 39, 40 we did not detect MD changes in the PUT or other basal ganglia structures (CN and GP) in the current study. Consistent with our findings, Tsukamoto et al reported no MD changes in the PUT of PSP patients.…”
Section: Discussioncontrasting
confidence: 79%
“…Differences among groups in each size measurement. A similar tendency was observed in recent studies 6,20,22. Reduced midbrain length (C) or area (D) in patients with PSP or CBS.…”
supporting
confidence: 88%
“…6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, it takes less time to measure the anteroposterior diameter than the area. 6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, it takes less time to measure the anteroposterior diameter than the area.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, MRPI has been widely proposed to support clinicians in the difficult task of differentiating clinically patients with PSP from those with PD or those with other parkinsonisms . A recent study from the MDS‐endorsed group for PSP stated that the P/M and MRPI were the most reliable biomarkers for diagnosing PSP‐RS both in the early and late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging measurements have been shown to be useful for diagnosing PSP . The MR Parkinsonism Index (MRPI) has proven to be an accurate biomarker for diagnosing patients with PSP and for predicting the clinical evolution toward PSP phenotypes of patients affected by undetermined parkinsonism or the appearance of vertical supranuclear gaze palsy (VSGP) in patients with PSP‐P . Overall, this biomarker is highly accurate in diagnosing PSP‐RS but shows a low sensitivity in distinguishing between patients with PSP‐P and those with PD .…”
mentioning
confidence: 99%